2005
DOI: 10.1016/j.jmoneco.2004.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of money in two alternative models: When is the Friedman rule optimal, and why?

Abstract: In models of money with an infinitely-lived representative agent (ILRA models), the optimal monetary policy is almost always the Friedman rule. Overlapping generations (OG) models are different: in this paper, we study how they are different, and why. We investigate the welfare properties of monetary policy in a simple OG model under two different types of money demand specifications and under two alternative assumptions about the generational timing of taxes for money retirement. We find that the Friedman rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 28 publications
(67 reference statements)
3
52
0
Order By: Relevance
“…Weiss (1980), Freeman (1985Freeman ( , 1989Freeman ( , 1993, and Smith (2002) all present examples of overlapping-generations models in which the Friedman rule fails to maximize private agents' steady-state utility. Bhattacharya, Haslag, and Russell (2004) unify and explain these results by tracing them back to distributional effects that are absent in representative-agent models like Krugman's and Svensson's. This paper also shows that distributional effects-the same distributional effects, as a matter of fact, that give rise to the real balance effect-operate once population growth is introduced into Krugman's cash-in-advance model.…”
Section: Old Ideas New Modelsmentioning
confidence: 80%
See 2 more Smart Citations
“…Weiss (1980), Freeman (1985Freeman ( , 1989Freeman ( , 1993, and Smith (2002) all present examples of overlapping-generations models in which the Friedman rule fails to maximize private agents' steady-state utility. Bhattacharya, Haslag, and Russell (2004) unify and explain these results by tracing them back to distributional effects that are absent in representative-agent models like Krugman's and Svensson's. This paper also shows that distributional effects-the same distributional effects, as a matter of fact, that give rise to the real balance effect-operate once population growth is introduced into Krugman's cash-in-advance model.…”
Section: Old Ideas New Modelsmentioning
confidence: 80%
“…Smith (2002) all present examples of overlapping-generations models in which the Friedman rule fails to maximize steady-state utility; Bhattacharya, Haslag, and Russell (2004) unify these examples by arguing that, in each case, monetary contraction has distributional effects of exactly the same kind as occur in the model with infinitely lived agents studied here.…”
Section: The Welfare Costs Of Deflationmentioning
confidence: 81%
See 1 more Smart Citation
“…By de…nition, such economies are dynamically e¢ cient. Bhattacharya, Haslag, and Russell (2005) and others have demonstrated that linear storage random relocation economies, irrespective of the degree of risk aversion, always return a verdict in favor of zero in ‡ation. Here, in contrast we are able to show, for example, that for logarithmic utility, zero in ‡ation is never optimal if the economy is dynamically e¢ cient.…”
Section: Model)mentioning
confidence: 99%
“…Weiss (1980) and Drazen (1981) studied superneutrality in an overlapping generations model without operative bequests and showed that inflation indeed stimulates capital formation, thus reaffirming the Tobin effect. In perhaps the most advanced treatment of the issue, Abel (1987) and Gahvari (1988Gahvari ( , 2007 noted a subtle issue with the preceding studies: Money creation redistributes income among generations; see also Crettez et al (1999), Bhattacharya et al (2005) and Ireland (2005). While policy changes are not superneutral per se, the government might make them effectively superneutral by using suitable lump-sum taxes and transfers.…”
Section: Introductionmentioning
confidence: 99%